2017
DOI: 10.1080/00365521.2017.1379557
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal endoscopic submucosal dissection (ESD) in the West – when can satisfactory results be obtained? A single-operator learning curve analysis

Abstract: We have proved that in the setting of the Western center, colorectal ESD can yield excellent results. It seems that the key to the success during the learning period is 'tailoring' lesions qualification guidelines to the experience of the endoscopist, as lesions diameter and localization highly influence the outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 33 publications
4
27
0
Order By: Relevance
“…Major challenges for implementing ESD in western countries comprise a long learning curve, high risk of complications, lack of structured training programs, few suitable starting cases in the stomach, and lack of experts 16 17 18 19 20 21 . Although there has been an increase in the number of published reports on colorectal ESD from western countries the majority of these are relatively small containing less than 100 cases with few exceptions 8 9 22 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Major challenges for implementing ESD in western countries comprise a long learning curve, high risk of complications, lack of structured training programs, few suitable starting cases in the stomach, and lack of experts 16 17 18 19 20 21 . Although there has been an increase in the number of published reports on colorectal ESD from western countries the majority of these are relatively small containing less than 100 cases with few exceptions 8 9 22 23 .…”
Section: Introductionmentioning
confidence: 99%
“…One study was not included because the R0 resection rate of colorectal ESD could not be determined [22]. Thus, after application of our inclusion and exclusion criteria, 15 European full-text studies of colorectal ESD published between 2007 and 2018 were included in this review (Table 1) [15,[23][24][25][26][27][28][29][30][31][32][33][34][35][36]. All these included studies were case series.…”
Section: Literature Searchmentioning
confidence: 99%
“…Due to the relatively difficult manoeuvrability of the colon and its thin wall, colorectal ESD is associated with increased procedure time and risk of perforation, which has contributed to the slow dissemination of ESD in western countries [10]. Major obstacles for implementing ESD in Europe comprise long learning curve, high risk of complications, lack of structured training programs, few suitable starting cases in the stomach, and lack of experts [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, these techniques have shown better results than conventional ESD, especially in terms of safety, even when performed by an endoscopist with minimal experience in ESD (less than 50 real procedures). This is noteworthy, owing to the fact that in western countries as far as it is known, expertise in ESD is hardly ever achieved at the beginning of the learning period [2,13]. In a recent observational study [14], lack of counter traction guided by gravity has shown to be an independent predictive factor for difficult ESD, so it is develop of devices to help to overcome this drawback is required.…”
Section: Discussionmentioning
confidence: 99%